Globalized Fatherhood - Inhorn, Marcia Claire; Chavkin, Wendy; Navarro, José-Alberto (Fertility, reproduction and sexuality, 2014)
Using an entirely new conceptual vocabulary through which to understand men's experiences and expectations at the dawn of the twenty-first century, this path-breaking volume focuses on fatherhood around the globe, including transformations in fathering, fatherhood, and family life. It includes new work by anthropologists, sociologists, and cultural geographers, working in settings from Peru to India to Vietnam. Each chapter suggests that men are responding to globalizationas fathersin creative and unprecedented ways, not only in the West, but also in numerous global locations.